1985
DOI: 10.1111/j.1365-2885.1985.tb00940.x
|View full text |Cite
|
Sign up to set email alerts
|

The effect of prostaglandin E1 on motility of the equine gut

Abstract: Prostaglandin E1 was infused intravenously (25, 50 and 75 ng/kg/min) in three ponies. Changes in gastrointestinal mechanical and electrical activity were recorded from chronically implanted strain-gauge force transducers and electrodes. Dose-dependent responses were obtained: there were significant decreases in electrical spiking activity in the stomach, left large colon and small colon, with a corresponding decrease of activity in the left dorsal colon mechanogram. The small intestine was also affected, showi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
29
0

Year Published

1998
1998
2017
2017

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(31 citation statements)
references
References 15 publications
2
29
0
Order By: Relevance
“…The Force Transducer method [19] is a laparotomic approach designed to quantitatively measure and record the contraction frequency, strength and tension in conscious subjects using a Force Transducer chronically attached to the serous membrane of the alimentary tract. It is not feasible, however, to apply this method in clinical practice for race horses.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The Force Transducer method [19] is a laparotomic approach designed to quantitatively measure and record the contraction frequency, strength and tension in conscious subjects using a Force Transducer chronically attached to the serous membrane of the alimentary tract. It is not feasible, however, to apply this method in clinical practice for race horses.…”
Section: Discussionmentioning
confidence: 99%
“…The analysis of equine digestive motility provides useful data for diagnosing and monitoring theraphy of these cases. Equine digestive motility has been studied employing electromyograms [16, 20, 24-26, 30, 31] and strain gauge force transducers (Force Transducers) [19] in ponies. Both these methods, however, require surgery.…”
Section: Measuring Methods With Ecgmentioning
confidence: 99%
“…The analysis of equine digestive motility provides useful data for diagnosing and monitoring therapy of these cases. Although there have been a number of reports regarding intestinal motility in ponies and foals [9,[12][13][14]17], there have been few studies focusing on adult horses [6]. In monogastric animals such as humans and dogs, it has been reported that motilin, a digestive hormone, plays some roles in the regulation of gastrointestinal motility [7,19,20].…”
mentioning
confidence: 99%
“…employed by Hunrt [6]. That is, the abdomen was opened by median section to expose the cecum, and one Force Transducer unit was fixed on the serous membrane of the bottom of the cecum with a 4-0 nylon suture to detect the contractions of the annular muscle.…”
mentioning
confidence: 99%
See 1 more Smart Citation